Jobinianas de Sérgio Assad - Análise dos procedimentos composicionais - Silva, Armando César da (2018)
Sérgio Assad (1952) is a composer who plays an important role in the current musical environment. He has already produced works for solo guitar, duos, trios, quartets, concerts and other formations. His compositions contribute to the expansion of the repertoire of music, as well as employing several compositional techniques that intensify the interest of musicians in his production. Assad also refers to ancient musical forms, Brazilian musical genres, Impressionist aesthetics and Jazz. This work sought to investigate the compositional procedures employed by Sérgio Assad in his series Jobinianas (nº 1, 2, 3 and 4), as well as the position of the composer before the different cultural manifestations in contemporary society. This research has been carried out more systematically, however, the number of works that discuss the compositional processes of Sérgio Assad is scarce, since this composer has an important artistic production for the concert guitar. Despite forming a sequence, the Jobinianas were composed in different periods, which may show us a bit of the process of evolution of Assad as a composer. To fulfill the goals of this work, we analyzed Assad 's compositional techniques, the influence of Tom Jobim's compositional aesthetics on the Jobinianas, and how popular music, mainly Brazilian music, is inserted in his compositions. To better meet the objectives and provide theoretical support regarding Assad's position as a composer, we have raised some discussions about postmodernism, hybridism and intertextuality in music.